Peningkatan Standar Pelayanan Minimal Di Kantor Dinas Penanaman Modal Dan Ptsp Kabupaten Enrekang - Yusriani, Yusriani; Hakim, Lukman; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to determine organizational communication in the One Stop Investment and Integrated Service Office, to know the minimum service standards that exist in the One Stop Investment and Integrated Service Office, and to find out how strong influence organizational communication had on the improvement of minimum service standards at The Office of Investment and One Stop Services of Enrekang Regency. This study used quantitative methods. The research data were collected using data collection techniques using a questionnaire  in the form of a checklist and documentation. The data were analyzed using descriptive statistics with a simple linear regression formula. The data was explained in the form of tables, the frequency and narrative results of the processed data with the help of SPSS. The results showed that there was an influence of organizational communication on improving the minimum service standards in the Office of Investment and One Stop Services in Enrekang Regency which was very significant, namely the value of t count t table = (10.473 1.675), so Ho was rejected, meaning that there was a significant effect.  Keywords: Influence, Organizational Communication, Minimum Service Standards